Improved cultivation of Pediococcus acidilactici by in situ removal of lactic acid using polymeric resin - Othman, Majdiah (2017)
Lactic acid bacteria (LAB) are industrially important microorganisms recognized for fermentative ability mostly in their probiotic benefits as well as lactic acid production for various applications. Nevertheless, fermentation employing LAB often suffers end-product inhibition which reduces the cell growth rate and the production of metabolite. The inhibition of lactic acid is due to the solubility of the undissociated lactic acid within the cytoplasmic membrane and insolubility of dissociated lactate, which causes acidification of cytoplasm and failure of proton motive forces. This phenomenon influences the transmembrane pH gradient and decreases the amount of energy available for cell growth. The utility of adsorbent resins for in-situ lactic acid removal to enhance the cultivation performance of Pediococcus acidilactici was studied in shake flask culture and 2 L stirred tank bioreactor. Five different types of anion-exchange resin (namely Amberlite IRA 67, IRA 410, IRA 400, Duolite A7 and Bowex MSA) were screened for the highest uptake capacity of lactic acid based on Langmuir adsorption isotherm. Weak base anion-exchange resin, Amberlite IRA 67 gave the highest maximum uptake capacity of lactic acid (0.996 g lactic acid/g wet resin) compared to the other anion-exchange resins. The effect of different loading concentrations (5 - 40 g/L) of anion-exchange resin on the performance of batch cultivation of P. acidilactici was also evaluated. High loading concentrations of anion-exchange resin showed an inhibitory effect on the growth of P. acidilactici. The application of IRA 67 anion-exchange resin in batch and constant fed-batch fermentation improved the growth of P. acidilactici about 67 times and 56 times, respectively compared to the control batch fermentation without resin addition. Nevertheless, the in situ addition of dispersed resin in the culture created shear stress by resins collision and caused direct shear force to the cells. The growth of P. acidilactici in the integrated bioreactor-internal column system containing anion-exchange resin was further improved by 1.4 times over that obtained in the bioreactor containing dispersed resin. The improvement of the P. acidilactici growth indicated that extractive fermentation using solid phase is an effective approach for reducing by-product inhibition and increasing product titer.